Economy of sufficiency: Essays on wealth in diversity, enjoyable limits and creating commons - Uwe Schneidewind; Tilman Santarius; Anja Humburg (Wuppertal Institut für Klima, Umwelt, Energie, 2014)
Another summit of change, known as Rio+20, has passed in summer 2012, nourishing the rumours of a green economy. Building up a green economy seems to be the all over recipe for different crises of capitalism, among them climate change and resource scarcity. Yet efficiency and consistency, as their main strategies, do not suffice to reach sustainable levels, as they cause rebound effects and keep stimulating economy growth. Obviously, there are limits to green growth, too. Can we conceive an economy, and respective economic institutions, that serve human needs and wealth without a built-in necessity to grow? What kind of political, mental, and individual changes does a sufficiency economy require? And what are perspectives and policies to actually start implementing it? Just before Rio +20 the symposium "Economy of Sufficiency", devoted to Wolfgang Sachs on the occasion of his 65th birthday in 2011, examined these questions in three dimensions. Accordingly this selection of contributions to the symposium follows the chapters "Wealth in diversity" (Ashok Khosla, Marianne Gronemeyer, Vandana Shiva), "Enjoyable limits" (Richard B. Norgaard, Tim Jackson) and "Creating commons" (Ezio Manzini, Silke Helfrich). The essays indicate the historical development of the ideas on a sufficiency economy. Wandering through discourses of sustainable development for several decades, the authors map the range of perspectives, practices as well as barriers and bridge them between cultures, agencies and schools. – – Im Sommer 2012 zog erneut ein Weltgipfel der Veränderung vorüber, bekannt unter dem Kürzel Rio+20. Er nährte die Hoffnungen um eine Green Economy, die im Gewand eines Allheilmittels für verschiedenste Krisen des Kapitalismus, darunter der Klimawandel und die Ressourcenknappheit, auf der Bühne stand. Doch es zeigte sich, dass die Hauptstrategien Effizienz und Konsistenz nicht ausreichen, um diese Krisen zu bewältigen und die wirtschaftliche Aktivität auf ein nachhaltiges Niveau einzupendeln. Denn mit diesen Strategien gehen Rebound-Effekte einher und sie erzeugen wieder neues Wirtschaftswachstum auf Kosten der natürlichen Lebensgrundlagen. Es gibt offensichtlich Grenzen auch für ein Grünes Wachstum. Können wir uns eine Wirtschaftsweise samt wirtschaftlicher Einrichtungen vorstellen, die menschlichen Bedürfnissen dienen und einen Wohlstand schaffen ohne die Triebfeder des Wachstums? Welcher Art von politischem, geistigem und individuellem Wandel bedarf es, um eine Ökonomie des Genug, eine Ökonomie der Suffizienz zu etablieren? Unmittelbar vor Rio+20 fand das Symposium "Economy of Sufficiency" (Ökonomie des Genug) anlässlich des 65. Geburtstags von Wolfgang Sachs im Jahr zuvor statt, das diesen Fragen in drei Dimensionen nachging. Endsprechend sind hier ausgesuchte Beiträge des Symposiums als Essays in den Kapiteln "Wealth in diversity" (Ashok Khosla, Marianne Gronemeyer, Vandana Shiva), "Enjoyable limits" (Richard B. Norgaard, Tim Jackson) und "Creating commons" (Ezio Manzini, Silke Helfrich) versammelt. Die Essays markieren die historische Ideenentwicklung einer Suffizienzökonomie. Auf der Wanderung durch die Nachhaltigkeitsdiskurse vieler Dekaden, kartieren die Autor(inn)en die Vielzahl an Perspektiven und Praktiken genauso wie die Hürden. Und sie schlagen dabei Brücken zu Kulturen, Kräfte und Schulen dieses Diskurses.
urn:nbn:de:bsz:wup4-opus-51915
Keywords: 330